Influence of aggregate sizes and packing combination on the properties of pervious concrete - Arcolezi, Karina Hwang [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Pervious concrete is a construction material that can be used as a pervious pavement and appears as a potential mitigator of floods and other problems related to soil waterproofing. Developing an efficient pervious concrete is crucial to promote its use on a large scale. This study aims to evaluate the effect of basaltic aggregates packing throughout maximum density methodology on the properties of pervious concrete. To this end, an experimental program related to using maximum density methodology for packing aggregates is presented to improve the mechanical properties of pervious concrete. The pervious concrete was produced using three different aggregates granulometry and their combinations using the packing with the maximum density methodology. The pervious concrete's physical, mechanical and hydraulic properties were determined for concretes after 28 days of curing, yielding up to 18 MPa in compressive strength with porosities varying between 25 and 35% and without significantly impairing the permeability of the pervious concrete. A multiple regression model was carried out for statistical analysis of the results. The results indicate that the compressive strength is significantly more influenced by the density and size of the aggregate. In contrast, the impact resistance was influenced by all parameters (density, porosity, and aggregate size). Thus, in addition to the improved properties demonstrated, the use of pervious concrete can also reduce the environmental problems associated with flooding from rainwater on pavements, contributing to sustainable development.

O concreto permeável é um material de construção que pode ser utilizado como pavimento permeável e aparece como um potencial mitigador de enchentes e outros problemas relacionados à impermeabilização do solo. O desenvolvimento de concreto permeável eficiente é uma questão crucial para promover seu uso em larga escala. Este estudo tem como objetivo avaliar o efeito do empacotamento de agregados basálticos através da metodologia de densidade máxima nas propriedades do concreto permeável. Para tal, é apresentado um programa experimental relacionado ao uso da metodologia de densidade máxima para o empacotamento dos agregados com o intuito de melhorar as propriedades mecânicas do concreto permeável. Os concretos permeáveis foram produzidos usando três diferentes granulometrias de agregados e suas combinações usando o empacotamento com a metodologia de densidade máxima. As propriedades físicas, mecânicas e hidráulicas do concreto permeável foram determinadas para concretos após 28 dias de cura, rendendo até 18 MPa na resistência à compressão com porosidades variando entre 25 e 35% e sem prejudicar significativamente a permeabilidade do concreto permeável. Para análise estatística dos resultados, foi realizado, um modelo de regressão múltipla, os resultados indicam que a resistência à compressão é significativamente mais influenciada pela densidade e tamanho do agregado. Enquanto que a resistência ao impacto foi influenciada por todos os parâmetros (densidade, porosidade e tamanho do agregado). Assim, além das propriedades aprimoradas demonstradas, o uso de concreto permeável também pode reduzir os problemas ambientais associados ao alagamento provenientes de águas pluviais em pavimentos contribuindo para o desenvolvimento sustentável.
Influência da dimensão e combinações de empacotamento dos agregados nas propriedades do concreto permeável
Keywords: Concreto permeável; Empacotamento de agregados; Densidade máxima; Estrutura de poros; Propriedades mecânicas; Pervious concrete; Aggregate packing; Maximum density; Pore structure; Mechanical properties